The Accumulation Characteristics of Different Heavy Metals in Sea Rice - Jiachun Li; Xu Yang; Yuze Zheng; Lele Tang; Zhenai Lai; Na Liu; Huashou Li (Applied Sciences, 2022)
Here heavy metal (Cd, Zn, and Cu) accumulation features of sea rice (a salt-tolerant rice cultivar) were explored to provide a reference for preventing and controlling of heavy metals, screen new plant remediation resources, and offer the basis for safe sea rice production. The sea rice variety Hai Hong 12 (HH12) was used as the research object in the soil culture experiments conducted to investigate the effects of the addition of Cd (0, 1, 2, 4, 8 mg/kg), Zn (0, 100, 200, 300, 400 mg/kg), and Cu (0, 100, 200, 300, 400 mg/kg) on the growth and accumulation of heavy metals in different HH12 parts. At different Cd and Zn concentrations, the root biomass of HH12 decreased significantly and the shoot biomass showed no marked difference; however, Cu stress inhibited the rice biomass. The Cd content in different parts of sea rice increased with an increase in Cd levels. At 8 mg/kg, shoot and spike had the highest Cd content, which was 89.02 and 45.37 mg/kg, respectively. At 1 mg/kg Cd concentration, the Cd transport coefficient of sea rice was the highest (1.36). The Zn content was the highest in sea rice at 400 mg/kg Zn. Zn concentrations in the shoot and spike were 440.95 and 175.51 mg/kg. However, the Zn transport coefficients of all parts were <1 at different Zn concentrations. Sea rice growth was severely hampered by high Cu stress (400 mg/kg). After 200 mg/kg Cu treatment, the highest Cu content was 82.85 mg/kg in shoot and 46.97 mg/kg in spike. The Cu transport coefficients of all parts were also <1 under Cu stress and decreased with an increase in the Cu concentration. In summary, HH12 exhibited a high risk of Cd accumulation, and Cd was more likely to be transported to the grains. Zn accumulation in sea rice had no obvious toxicity to its shoot growth, but its shoot had a slight risk of Zn accumulation. Cu was mostly built up in the HH12 roots, but its ability to move around was low. However, high Cu concentrations slowed the growth of sea rice.